Influencia del talento humano en la satisfacción del personal de la municipalidad distrital del Napo - Barba Mori, Franco Domingo Ontere (2018)
The 21st century is characterized by the actions of different agents in a context of continuous change that affect political, economic, social and educational reality; the future that will surely continue to be marked by the change will provoke an environment that is increasingly complex and difficult to predict. Thus, organizations must act beyond traditional management systems to be able to differentiate and be more competitive. The economic development and growth of all productive sectors of the Napo district, they have to take on this challenge, which will allow to be a benchmark at the district, provincial, regional and national levels. Organizational Development remains in force, wrapped up in new terms such as knowledge management, intellectual capital, structural capital, relational capital, etc. However, people, customers and technology are still the managers' concern, so it is essential to describe how the scientific knowledge of the Human Talent Management model has evolved over time. Recently, it is observed that there are fewer and fewer institutions that do not invest in human resources. Various investigations indicate that since companies have already realized that after investing in infrastructure, technology, etc., the expected results are not obtained because they do not give the importance that the development of the workers deserves, they are making a 180º in the development of ethical policies and strategies for the benefit of the worker (Gardner, 2007, Ornelas, 2006, Charan, 2006) which will have a positive impact on the development of the organization and will overcome the inconveniences that the change is causing.